Factor analysis of the everyday memory questionnaire in persons with traumatic brain injury. Issue 3 (3rd April 2018) - Sander, Angelle M.; Clark, Allison N.; van Veldhoven, Laura M.; Hanks, Robin; Hart, Tessa; Leon Novelo, Luis; Ngan, Esther; Arciniegas, David B.
Abstract: Objectives: To investigate the factor structure of the Everyday Memory Questionnaire (EMQ) in persons with traumatic brain injury (TBI).Method: This was a secondary analysis of baseline data from two clinical trials targeting memory impairment after TBI. Participants were 169 persons with complicated mild, moderate, or severe TBI at an average of 41 months post-injury. They completed the EMQ via clinical interview. Exploratory factor analysis was conducted using a three-factor principal axis factoring estimation method with a polychoric correlation matrix and oblique rotation.Results: The three factors accounted for 49.2% of the variance, with moderate correlations observed among the factors. The three factors appeared to represent general everyday memory (prospective and episodic), conversational memory, and spatial or action memory. The three factors added significantly to the variance in age-corrected objective learning test scores predicted by injury severity, education, and sex.Conclusions: The three factors of the EMQ are consistent with the heterogeneity of memory impairments observed after TBI. The factor scores may be used to target treatments for impaired memory and to evaluate their effectiveness.